The place of the oral examination in today's assessment systems - Davis, M.H.; Karunathilake, I.M. (My University, 2005)
The oral examination or viva is a traditional form of assessment in which one or more examiners fire questions at the candidate. It typically takes the form of an interview or discussion between the examiners and candidate and happens in an examination hall or other such setting away from patients. It should be distinguished from other types of oral examination such as the long and short case, which take place in the presence of the patient or are focused around a patient seen by the candidate and the oral that is used for defence of written work such as a thesis. The oral examination is said to assess knowledge, to probe depth of knowledge and to test other qualities such as mental agility.....